Ginsenoside Rg1 Attenuates Oligomeric Aβ1-42-Induced Mitochondrial Dysfunction - Huang, Tianwen; Fang, Fang; Chen, Limin; Zhu, Yuangui; Zhang, Jing; Chen, Xiaochun; Shidu Yan, Shirley (Current Alzheimer Research, 2012)
Mitochondrial dysfunction is one of the major pathological changes seen in Alzheimer’s disease (AD). Amyloid beta-peptide (Aβ), a neurotoxic peptide, accumulates in the brain of AD subjects and mediates mitochondrial and neuronal stress. Therefore, protecting mitochondrion from Aβ-induced toxicity holds potential benefits for halting and treating and perhaps preventing AD. Here, we report that administration of ginsenoside Rg1, a known neuroprotective drug, to primary cultured cortical neurons, rescues Aβ-mediated mitochondrial dysfunction as shown by increases in mitochondrial membrane potential, ATP levels, activity of cytochrome c oxidase (a key enzyme associated with mitochondrial respiratory function), and decreases in cytochrome c release. The protective effects of Rg1 on mitochondrial dysfunction correlate to neuronal injury in the presence of Aβ. This finding suggests that ginsenoside Rg1 may attenuate Aβ-induced neuronal death through the suppression of intracellular mitochondrial oxidative stress and may rescue neurons in AD.
Keywords: cell lysis